Public Morals and Homosexuality: The Kaos GL v. Turkey Judgment - Esen, Egemen (Seçkin Yayıncılık, 2017)
The European Court of Human Rights leaves an “elbow room” to the national authorities in limiting the rights granted in the Convention under the doctrine of the margin of appreciation. At the Kaos GL v. Turkey judgment, it was assessed whether or not confiscating all the copies of the magazine on the grounds of public moral was a proportionate interference in the freedom of expression. The topic of the magazine was pornography. Besides, the magazine belongs to the association which defends LGBT rights. It is obvious that interference in the freedom of expression was made with a discriminatory motive. In this study, the legislation that justified the interference has been evaluated. In addition, it has been stated that the Court should have assessed the censorship in the context of the discrimination under the Article 14 of the Convention in conjunction with Article 10.
Keywords: Freedom of artistic expression, KaosGL, Prohibition of Discrimination, Margin of appreciation, Public Morals